The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3389/fnagi.2014.00044
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics of Post-Stroke Angiogenesis in the Aged Brain

Abstract: Despite the obvious clinical significance of post-stroke angiogenesis in aged subjects, a detailed transcriptomic analysis of post-stroke angiogenesis has not yet been undertaken in an aged experimental model. In this study, by combining stroke transcriptomics with immunohistochemistry in aged rats and post-stroke patients, we sought to identify an age-specific gene expression pattern that may characterize the angiogenic process after stroke. We found that both young and old infarcted rats initiated vigorous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 94 publications
(116 reference statements)
6
98
0
Order By: Relevance
“…Probably early post-ischemic Alzheimer-related gene dysregulation triggers delayed gene dysfunction in post-stroke patients and old ischemic rats [57][58][59]. Buga et al [57][58][59] have identified an age-related gene expression pattern following brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably early post-ischemic Alzheimer-related gene dysregulation triggers delayed gene dysfunction in post-stroke patients and old ischemic rats [57][58][59]. Buga et al [57][58][59] have identified an age-related gene expression pattern following brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Buga et al [57][58][59] have identified an age-related gene expression pattern following brain ischemia. These studies indicated that genes specific for anxiety, depression, stress, and neuropathic syndrome had harmful response to ischemia in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were anesthetized and maintained throughout the procedure by inhalation of isoflurane (1-3% mixed with 97% O 2). For 3 wk before subcutaneous implantation, mice were trained by tail-cuff plethysmography (Kent Scientific, Torrington, CT) with baseline recording and during the 14 days of subcutaneous treatment, blood pressure (systolic, diastolic, and mean arterial pressures) and heart rate were noninvasively recorded on days 5,10,12, and 14 as previously described (3). For reference, blood pressure was also assessed under anesthesia by both Millar catheter and tail-cuff.…”
Section: Animalsmentioning
confidence: 99%
“…On the other hand, upregulation of angptl2 gene expression, among other genes, was recently reported in the aged brain of both rats and human, contributing to poststroke angiogenesis (5). Information of angptl2 involvement in regulating endothelial function, however, is limited.…”
mentioning
confidence: 99%
“…Our studies before showed that the combination of G-CSF and BMSCs increased new blood vessel formation in the infarct core generating an "regeneration islet" [33]. However, BMSCs therapy needs further investigation.…”
Section: Mesenchymal Stem Cells Transplantation In the Acute Phase Ofmentioning
confidence: 79%